BIOCHAR YANG DIPRODUKSI DENGAN TUNGKU DRUM TERTUTUP RETORT MEMBERIKAN PERTUMBUHAN TANAMAN YANG LEBIH TINGGI (BIOCHAR PRODUCED BY RETORT CLOSED DRUM KILN PROMOTES HIGHER PLANT GROWTH RATE) - Syahrinudin Syahrinudin; Arya Wijaya; Tunggul Butarbutar; Wahjuni Hartati; Ibrahim Ibrahim; Maurit Sipayung (ULIN: Jurnal Hutan Tropis, 2018)
ABSTRACTInterests on biochar application for the improvement of soil properties and fertily are increasing worldwide nowadays and numerous of production techniques are now available. This research was aimed at the investigation (a) on the characteristics biochar produced by 3 (three) different techniques, i.e: (1) traditional soil pit, (2) retort closed drum and (3) open drum kilns, as well as (b) on growth (height, leaf number and survival) response of Shorea leprosula seedling to 20%v biochar application on bioassay trial in the nursery. Bioassay trial was carried out in nursery of Forestry Faculty of Mulawarman University, Samarinda, Indonesia and was in accordance with Completely Randomized Design (CRD) applying 4 treatments and 3 replications.Of those 3 production techniques, retort closed drum kiln production technique was the most promising for further development and adoption providing not only that the biochar produced gave better properties and soil improvement capacity but also higher production recovery and less time and labour involvement. Furthermore, eventhough it was not statistically significant, biochar produced by retort closed drum gave better growth (height and leaf number) rate to S. leprosula seedlings in bioassay trial compared to those given by biochar produced by other techniques and without biochar treatments.